Pancasila as a Paradigm of Economic Development in Facing the Coronavirus Outbreak - Muhammad Guntur Nugroho; Meli Amalia; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This article aims to find out the concept of Pancasila values ​​as a paradigm of economic development in the face of the Coronavirus outbreak which must require togetherness and national unity so that it is not divided in the face of efforts to handle the Coronavirus. Pancasila as an economic development paradigm during the Coronavirus pandemic is based on the moral values ​​of Pancasila, in particular, the economic system must be based on morality following the first precepts teaching the value of faith and sincerity in dealing with the Coronavirus outbreak and continuing to build and restore the economy during a pandemic. for the welfare of the people based on kinship. Based on the second principle of Pancasila, socio-cultural development was developed based on respect for the various socio-cultural values ​​throughout Indonesia towards achieving a sense of unity as a nation so that humanitarian empathy must give birth to cooperation to solve problems, this togetherness will accelerate the handling of the Coronavirus pandemic, and does not escape the role of the third principle of Pancasila, namely helping each other, sharing, and collaborating regardless of race, ethnicity, and religion.